2021
DOI: 10.1001/jamaophthalmol.2021.1110
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity, Vitreous Hemorrhage, and Other Ocular Outcomes After Vitrectomy vs Aflibercept for Vitreous Hemorrhage Due to Diabetic Retinopathy

Abstract: IMPORTANCEAlthough there were no differences in mean visual acuity (VA) over 24 weeks after vitrectomy with panretinal photocoagulation (PRP) vs aflibercept in a randomized clinical trial among eyes with vitreous hemorrhage due to proliferative diabetic retinopathy (PDR), post hoc analyses may influence treatment choices.OBJECTIVE To compare exploratory outcomes between treatment groups that may affect treatment choices for patients with vitreous hemorrhage due to PDR. DESIGN, SETTING, AND PARTICIPANTSThis pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
(18 reference statements)
1
12
0
2
Order By: Relevance
“… 16 However, their study demonstrated faster recovery of vision when baseline vision was worse than 20/800 and quicker clearance of VH in eyes that underwent initial vitrectomy with PRP. 17 The current study and Protocol AB both demonstrated the safety and efficacy of PPV with PRP for PDR with VH; an optimal approach to PDR is still likely use of traditional first-line in-office options followed by PPV if necessary and indicated.…”
Section: Discussionmentioning
confidence: 62%
“… 16 However, their study demonstrated faster recovery of vision when baseline vision was worse than 20/800 and quicker clearance of VH in eyes that underwent initial vitrectomy with PRP. 17 The current study and Protocol AB both demonstrated the safety and efficacy of PPV with PRP for PDR with VH; an optimal approach to PDR is still likely use of traditional first-line in-office options followed by PPV if necessary and indicated.…”
Section: Discussionmentioning
confidence: 62%
“…Treten als Folge der diabetischen Retinopathie Komplikationen wie Netzhautablösung, Glaskörperblutung und/oder eine Rubeosis iridis auf, spricht man von einer fortgeschrittenen diabetischen Augenerkrankung. Neben Vitrektomie inklusive Entfernung eventuell vorhandener Netzhautmembranen und -traktionen und panretinaler Laserkoagulation (Netzhautablösung, Glaskörperblutung), sowie anti-VEGF IVOM (Glaskörperblutung [35,36]) können bei Sekundärglaukom auch zyklodestruktive (=den Ziliarkörper verödende) Verfahren wie Zyklophotokoagulation oder Implantation eines drucksenkenden Drains indiziert sein. Weitere Details zur Lizenz entnehmen Sie bitte der Lizenzinformation auf http://creativecommons.org/licenses/by/4.…”
Section: Fortgeschrittene Diabetische Augenerkrankungunclassified
“…Modern vitreoretinal surgery is safe and effective in treating various retinal disorders, including rhegmatogenous retinal detachment (RRD), [ 1 ] complications of diabetic retinopathy, [ 2 ] macular hole (MH), [ 3 ] and epiretinal membrane (ERM) [ 4 ]. However, since vitreoretinal surgery is invasive, postoperative complications, such as increased (2.5–61.5%) or decreased (1.8–13.1%) intraocular pressure (IOP), [ 5 10 ] corneal edema (0.80–1.1%) [ 7 , 11 ], intraocular inflammation (0.25–26%) [ 5 , 12 ], or retinal detachments (1.2–1.7%) may occur in patients [ 11 ].…”
Section: Intruductionmentioning
confidence: 99%